Prediksi Curah hujan di Kota Pekanbaru Menggunakan lSTM (Long Short Term Memory) - Hendra, Yos; Mukhtar, Harun; Baidarus; Hafsari, Rizka (Jurnal Rekayasa Perangkat Lunak dan Sistem Informasi, 2023)
Based on data obtained from BMKG Pekanbaru City in 2010-2020 there was an increase anddecrease in the intensity of rainfall that occurred in Pekanbaru city. The increase in rainfall in thecity of Pekanbaru will cause problems such as the occurrence of flooding of several roads and severalareas in the city of Pekanbaru and the occurrence of other unexpected disasters that will causeproblems and experience difficulties. In overcoming this problem, research was conducted in the formof Rainfall Prediction in Pekanbaru City Using LSTM (Long Short Term Memory) using 2 methods,namely in finding the accuracy of the error rate using RMSE (Root Mean Square Error) and MSE(Mean Square Error). The results showed that the predictions made were quite good. With the lowesterror rate of 21,328 in the train and 454,901 in the test, the composition of the train data and the testdata half gave the best results.